Contrasting effects of fire frequency on plant traits of three dominant perennial herbs from Chaco Serrano - Carbone, Lucas Manuel (2016)
Fil: Carbone, Lucas Manuel. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias. Herbario ACOR; Argentina.